ATIM-14. ALLIANCE A071101: A PHASE II RANDOMIZED TRIAL COMPARING THE EFFICACY OF HEAT SHOCK PROTEIN PEPTIDE COMPLEX-96 (HSPPC-96) VACCINE GIVEN WITH BEVACIZUMAB VERSUS BEVACIZUMAB ALONE IN THE TREATMENT OF SURGICALLY RESECTABLE RECURRENT GLIOBLASTOMA. (6th November 2017) - Bloch, Orin; Shi, Qian; Anderson, S Keith; Knopp, Michael; Raizer, Jeffrey; Clarke, Jennifer; Waziri, Allen; Colman, Howard; Bruce, Jeffrey; Olson, Jeffrey J; Schwerkoske, John; Parsa, Andrew; et al.
Abstract: BACKGROUND: Heat shock protein vaccines can be used to stimulate anti-tumor immune responses. An autologous vaccine (HSPPC-96) generated from patient resected tumors has been previously studied in single arm phase I/II trials for newly diagnosed and recurrent GBM. Based on promising survival in these studies, a randomized, multi-centered phase II trial of HSPPC-96 for recurrent GBM compared to bevacizumab was undertaken (NCT01814813). METHODS: Patients with 1 st /2 nd recurrence of resectable GBM were enrolled and underwent surgery with generation of HSPPC-96 from autologous tumors. Post-operative eligibility included a volumetric extent of resection ≥90% (by central review) and sufficient tumor to generate a minimum of 4 vaccine doses. Patients were randomized (1:1:1) to receive HSPPC-96 vaccine followed by bevacizumab at subsequent progression vs. concurrent HSPPC-96 vaccine and bevacizumab vs. bevacizumab alone. The primary endpoint was overall survival (OS) aiming to detect a 36% reduction in HR with 85% power and alpha=0.1 for pooled HSPPC-96 groups vs. bevacizumab alone. Planned enrollment was 165 patients (n=55/arm). An interim analysis was pre-planned at 50% of events (65 deaths). Secondary endpoints included progression-free survival and adverse events. RESULTS: At final analysis, 90 patients were enrolled with a distribution of 29:30:31. The study was terminated for futility after the interim analysis. In the intention to treat population, OS for the HSPPC-96 treated groups was 7.5 vs. 10.7 months for bevacizumab alone (HR=2.06 [95% CI 1.18–3.60], p=0.008). Among patients treated per protocol (n=73), OS for HSPPC-96 patients was 8.6 vs. 12.3 months (HR=1.99 [95% CI 1.03–3.81], p=0.03). Trends were similar for progression-free survival between groups. HSPPC-96 toxicity was well tolerated with no attributable serious adverse events. CONCLUSIONS: The study failed to demonstrate a survival benefit for patients treated with HSPPC-96 alone or in combination with bevacizumab compared to bevacizumab alone. Correlative analyses are ongoing. SUPPORT: U10CA180882, U10CA180821, U10CA180868, U24CA196171.